Desenvolvimento de vídeos sobre o software de simulação de circuitos LTspice - Silva, Lays Matinuzzo (Universidade Federal de São Carlos, 2025)
This article presents the production of a series of videos about the LTspice circuit simulation software. The software was chosen because it is reliable, free and easy to access, both for electrical engineering students and anyone else interested in electronics-related subjects. This project is an opportunity to update the video course developed in 2023 by the student Gabriel S. da Silva, since LTspice has undergone some changes in its interface due to updates. Eleven videos were developed, covering various LTspice features, also including examples and demonstrations of electronic circuits. The aim of this project is to expand at least some of the information acquired in academic circles to society in general, promoting the democratization of knowledge.
Development of videos about the LTspice circuit simulation software
Keywords: Software de simulação; LTspice; Vídeos; Youtube; ENGENHARIAS::ENGENHARIA ELETRICA::CIRCUITOS ELETRICOS, MAGNETICOS E ELETRONICOS